2014
DOI: 10.1007/s00540-014-1926-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 0.5 L 6 % hydroxyethyl starch 130/0.42 versus 1 L Ringer’s lactate preload on the hemodynamic status of parturients undergoing spinal anesthesia for elective cesarean delivery using arterial pulse contour analysis

Abstract: Preloading with 0.5 L HES 130/0.42 produced more stable hemodynamics compared to 1 L R/L solution in obstetric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…This was also previously demonstrated in previous double blind randomized controlled trials comparing the effect of preload or co-load techniques with HES versus crystalloid for mitigating hypotension due to spinal anesthesia during cesarean delivery [25]. In contrast other studies found significantly different vasopressor use between groups [26, 27]. Explanation for these findings can be related to variability in the amount and concentration of bupivacaine used as well as in study designs and endpoint definitions.…”
Section: Discussionsupporting
confidence: 54%
“…This was also previously demonstrated in previous double blind randomized controlled trials comparing the effect of preload or co-load techniques with HES versus crystalloid for mitigating hypotension due to spinal anesthesia during cesarean delivery [25]. In contrast other studies found significantly different vasopressor use between groups [26, 27]. Explanation for these findings can be related to variability in the amount and concentration of bupivacaine used as well as in study designs and endpoint definitions.…”
Section: Discussionsupporting
confidence: 54%
“…We included 109 out of 1021 retrieved trials, which included 8561 women (Fig. and see also Supporting Information, Table S1) . Twelve interventions (eleven active treatments and one inactive control) to prevent intra‐operative hypotension were studied, with 30 direct comparisons (see also Supporting Information, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…To prevent hypotension, a number of clinical approaches have been suggested, including volume loading, vasopressor administration and left uterine displacement. When performing spinal anaesthesia for caesarean delivery, it is critically important to identify patients at risk of hypotension, as it would afford anaesthesiologists the opportunity to prevent this phenomenon by taking measures such as pre‐anaesthesia volume expansion and prophylactic vasopressor administration …”
mentioning
confidence: 99%